Systematic literature review: analysis of implementation trends of STEM-based physics learning on dynamic fluid material - Brilliana Ghorbiy; Sutopo Sutopo; Endang Purwaningsih (Universitas Ahmad Dahlan, 2024)
This study aims to examine the implementation of STEM-based physics learning on dynamic fluid material. This research falls under the Systematic Literature Review (SLR) category using the PRISMA method. The databases used include Google Scholar, Journal of Physics: Conference Series, and AIP Conference Proceedings. From these three databases, six relevant articles were obtained. Based on the research review conducted, the findings indicate that STEM-based physics learning can enhance students' mastery of concepts and creative thinking skills in dynamic fluid materials. This study implies that implementing STEM-based physics learning on dynamic fluid materials can enhance students' conceptual understanding and creative thinking skills, potentially fostering innovation in physics education in the future.